2022
DOI: 10.3390/vaccines10111910
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Rates and Factors Affecting Vaccine Hesitancy among Pregnant Women during the Pandemic Period in Turkey: A Single-Center Experience

Abstract: The new coronavirus disease (COVID-19), which was detected in the Wuhan region of China in 2019 and spread rapidly all over the world, was declared a pandemic by the WHO in 2020. Since then, despite widespread recommendations to prevent the spread of the disease and provide treatment for sick people, 6,573,968 people died all over the world, 101,203 of which in Turkey. According to the international adult vaccination guidelines, pregnant women have been recommended to get vaccinated against the new coronavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…All the studies were performed in gynecological or maternal units at public or private hospitals. Recruitment was performed by inviting consecutive women attending the clinic in approximately half of the cases (n = 25/43) [2,20,[24][25][26]29,30,33,35,[37][38][39][40]42,44,46,47,49,[51][52][53][54]56,60,61], random sampling was employed in four studies (n = 4), antenatal care registry was used in three studies (n = 3) [21,36,59], convenience sampling was adopted in other three studies (n = 3) [27,28,32], multistage sampling approach was used in two studies (n = 2) [55,58], the snow-ball method was used in one study (n = 1) [22], and one study used data from an ongoing prospective longitudinal cohort study (n = 1) [50]. Four studies did not specify the recruitment method adopted [23,31,45,48].…”
Section: Main Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies were performed in gynecological or maternal units at public or private hospitals. Recruitment was performed by inviting consecutive women attending the clinic in approximately half of the cases (n = 25/43) [2,20,[24][25][26]29,30,33,35,[37][38][39][40]42,44,46,47,49,[51][52][53][54]56,60,61], random sampling was employed in four studies (n = 4), antenatal care registry was used in three studies (n = 3) [21,36,59], convenience sampling was adopted in other three studies (n = 3) [27,28,32], multistage sampling approach was used in two studies (n = 2) [55,58], the snow-ball method was used in one study (n = 1) [22], and one study used data from an ongoing prospective longitudinal cohort study (n = 1) [50]. Four studies did not specify the recruitment method adopted [23,31,45,48].…”
Section: Main Characteristics Of Included Studiesmentioning
confidence: 99%
“…In approximately half of the studies, questionnaires were administered face-to-face (n = 21/43) [2,21,26,30,34,35,[38][39][40][41][42][43][44][45][46][47][48]56,58,61], however, two of them combined the faceto-face interview with the on-line administration [44,61]. Seven studies used on-line administration [24,[27][28][29]33,54,60], five studies performed a self-administration (paperbased) [22,32,37,49,51] and two studies used a telephone administration [36,50].…”
Section: Main Characteristics Of Included Studiesmentioning
confidence: 99%
“…31 The Health Ministry of Turkey recommends COVID-19 vaccination before or during pregnancy, but vaccine acceptance is low in this group. 32 Although the birth rate in Turkey has decreased in recent years, with 14,894 births per 1000 people, it is still higher than that in most other countries. 33 For this reason many pregnant women have been admitted to the ICU during the COVID-19 pandemic in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study conducted in Western Kenya in 2020 revealed that 6% of pregnant women were diagnosed with COVID-19, compared to 4% of postpartum women [7]. Despite the risk, there are limited data on COVID-19 vaccination coverage and uptake during pregnancy in lower-middle-income countries [1], with vaccination rates ranging from 14.4% in Ethiopia [8] to 37.7% in Turkey [9]. Some possible explanations related to the lower rates of COVID-19 vaccination uptake include the lack of information on the safety of COVID-19 vaccines during pregnancy [10], vaccine hesitancy among healthcare providers [11], low susceptibility to COVID-19 [12], and concerns about rapid vaccine development [13].…”
Section: Introductionmentioning
confidence: 99%